ASSESSMENT OF PTEROYL-L-GLUTAMIC ACID BASED INHIBITORS TO MITIGATE SILICATE SCALES DURING ALKALINE-SURFACTANTPOLYMER FLOODING - ABUBAKAR, ABUBAKAR UMAR (2014)
Silicate scale may precipitate and deposit during Alkaline-Surfactant-Polymer (ASP) flooding, resulting in constriction to the flow of fluid during oil production. Unlike other traditional scales, silicate scales formation in the oil field is a complex and poorly understood. Among other factors, its precipitation largely depend on pH, temperature and divalent ions concentrations. Once formed, silicate scale is very difficult to remove and it has been removed via drilling in the past. However, removing scale by this method causes formation damage, among other disadvantages. In recent years, the chemical treatment has taken over in the treatment of silicate scales. In spite of the large volume of work carried out on chemical inhibitors, none has provided an effective method of controlling the troublesome silicate scale. Furthermore, conventional chemical inhibitors are subjected to increasing strict regulations. Therefore, alternative green scales inhibitors such as COM6 Polyaspartic acid, Pteroyl-L-glutamic acid (PGLU) are beginning to get attention. Aspartic acid is, together with glutamic acid, classified as an amino acid.